Victorious wives the disguised heroine in 19th-century Malay syair - Hijjas, Mulaika (Monographs of the Malaysian Branch, Royal Asiatic Society, 2011)
"In Victorious Wives, Mulaika Hijjas uses tools drawn from literary criticism and gender studies to look at a previously neglected corpus of Malay literature in a new light. The relatively equal gender relations in Southeast Asia have long been presented as a defining characteristic of the region, but there are few detailed case studies of pre-modern women or women's literature to illustrate this point, and studies of women in traditional literature have of necessity relied on texts that expressed masculine viewpoints. The syair of the Riau Archipelago that are the basis of this book, six nineteenth-century Malay narrative poems, are a unique exception in that they allow access to women's imaginative worlds, and they provide a significant historical backdrop to anthropological accounts of gender in the Malay world in modern times."--P. [4] of cover